(untitled) (Lex localis - Journal of Local Self-Government, 2020)
One of the legal forms of action to be applied by a commune for the care of homeless animals is to develop and implement homeless animal care programmes and prevent animal homelessness. The whole regulations examined below clearly demonstrate that the commune carries out its duties as mentioned above, cooperating with registered and legally operating animal shelters. Derogations from this principle may be regarded as the unlawful fulfilment of commune’s own tasks, which is the subject of an audit by the State Veterinary Inspectorate or the voivodeship governor. However, it may be difficult to make a clear identification of the legal nature of homeless animal care programmes and animal homelessness prevention as acts of local law or planning acts as internal law acts. The views of scholars and case-law on this issue are not uniform.